Learning Orientation and Perceived Parental Attitudes of Students at the Senior Secondary Level - Rammohan, Letha (JOURNAL OF INDIAN EDUCATION, 2010)
The study was conducted to examine the learning orientation of students at Senior Secondary level and also to explore its linkages with parental attitudes. The sample of 135 students studying in class XI and their respective parents (135 fathers &135 mothers) was drawn randomly from two Senior Secondary schools of Delhi. Two separate tools namely questionnaire for students and questionnaire for parents developed and validated by the researcher were used. The study brought out clearly shows that interest orientation was the most influencing factor in learning.Career orientation of students was linked with interest orientation and examination orientation. The study also revealed that students at senior secondary level generally had high orientation towards exams and career. There was no significant difference between boys and girls regarding their approach to exams and career. Also parental influence especially parental support affected the learning orientation of children.